Probabilistic Template of the Lateral Parabrachial Nucleus, Medial Parabrachial Nucleus, Vestibular Nuclei Complex, and Medullary Viscero-Sensory-Motor Nuclei Complex in Living Humans From 7 Tesla MRI - Singh, Kavita; Indovina, Iole; Augustinack, Jean C.; Nestor, Kimberly; García-Gomar, María G.; Staab, Jeffrey P.; Bianciardi, Marta (Frontiers in Neuroscience, 2020)
The lateral parabrachial nucleus, medial parabrachial nucleus, vestibular nuclei complex and medullary viscero-sensory-motor nuclei complex (the latter including among others the solitary nucleus, vagus nerve nucleus, and hypoglossal nucleus) are anatomically and functionally connected brainstem gray-matter structures that convey signals across multiple modalities between the brain and the spinal cord to regulate vital bodily functions. It is remarkably difficult to precisely extrapolate the location of these nuclei from ex vivo atlases to conventional 3 Tesla in vivo images; thus, a probabilistic brainstem template in stereotaxic neuroimaging space in living humans is needed. We delineated these nuclei using single-subject high contrast 1.1 mm isotropic resolution 7 Tesla MRI images. After precise coregistration of nuclei labels to stereotaxic space, we generated a probabilistic template of their anatomical locations. Finally, we validated the nuclei labels in the template by assessing their inter-rater agreement, consistency across subjects and volumes. We also performed a preliminary comparison of their location and microstructural properties to histologic sections of a postmortem human brainstem specimen. In future, the resulting probabilistic template of these brainstem nuclei in stereotaxic space may assist researchers and clinicians in evaluating autonomic, vestibular and viscero-sensory-motor nuclei structure, function and connectivity in living humans using conventional 3 Tesla MRI scanners.